Changes in soil quality under conservation agriculture practices in West Nusa Tenggara, Indonesia - Achmad Rachman (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2018)
The main challenge for cultivating upland in semi arid environment as in West Nusa Tenggara, Indonesia is the limited availability of water resources and accelerated deterioration of soil quality. This study evaluated changes in selected soil properties and soil quality 4 years after the implementation of conservation agriculture (CA) practices. The study was conducted at the CA demonstation plots in Gunung Malang Village, Pringgabaya District, East Lombok Regency, West Nusa Tenggara Province. The surface soil texture was loam with slope ranging from 5 to 10%. Two CA Models and one farmer practice (LP) were compared. Within each model three sampling positions were sampled: within the corn planted area (Position A), 0-10 cm from the edge of the corn planted area (Position B), and 10 – 20 cm from the edge of the corn planted area (Position C). Intact soil samples (76 by 40 mm) were taken from the three positions at two depths (100-mm increments) to determine soil physical properties and bulk samples from the surface soil (0 – 15 cm) to determine soil chemical properties in the laboratory. The CA Model had significantly (P < 0.01) lower bulk density (BD), and increase soil organic carbon (SOC) and available P (Av P), while Position had significantly affect only BD. The lowest BD (0.87 ± 0.07 Mg m-3) and the highest SOC (1.51± 0.05%) and available pore water (AWC; 18.06 ± 0.76% vol) were found at Position A in CA with permanent pit (PIT). The highest soil quality index was found in Position A followed by Position B and the least was in C indicating that the crop rotation component in CA had relatively small effect on improving soil quality. These results suggested that there is a gradual improvement on soil quality after 4 years of the implementation of conservation agriculture and require longer time than 4 yr to achieve the best soil quality for this semi arid environment